1986
DOI: 10.1172/jci112742
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay of growth hormone-dependent insulinlike growth factor binding protein in human plasma.

Abstract: A specific radioimmunoassay has been established for a growth hormone-dependent insulinlike growth factor (IGF) binding protein (BP) from human plasma. Although the assay was directed against a 53-kD, acid-stable BP subunit, the main immunoreactive BP in the circulation had an apparent molecular mass of -125 kD. Only higher primate species showed crossreactivity, and IGF-I, IGF-II, and other peptides were without effect. Circulating BP levels in healthy subjects rose threefold from early childhood to puberty. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
195
3
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 532 publications
(218 citation statements)
references
References 36 publications
19
195
3
1
Order By: Relevance
“…1) as has been previously reported in this latter group [23,27,36], Bang et al [37] have recently reported that basal immunoreactive IGFBP-3 levels in type 2 diabetic patients do not differ from those measured in healthy obese and non-obese subjects. The discrepancy between our data and theirs may only be apparent and ascribed to differences in the respective protocols.…”
Section: Discussionsupporting
confidence: 78%
“…1) as has been previously reported in this latter group [23,27,36], Bang et al [37] have recently reported that basal immunoreactive IGFBP-3 levels in type 2 diabetic patients do not differ from those measured in healthy obese and non-obese subjects. The discrepancy between our data and theirs may only be apparent and ascribed to differences in the respective protocols.…”
Section: Discussionsupporting
confidence: 78%
“…It is well known that nutritional status effects IGF-I levels more than IGFBP-3 levels (Baxter and Martin, 1986;Thissen et al, 1994). Low IGF-I levels were observed in chronic disease and malnutrition whereas IGFBP-3 remains relatively unchanged (Baxter and Martin, 1986;Thissen et al, 1994;Underwood et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Sera were assayed for immunoreactive IGFBP-3 and ALS as described previously (13,14). The lower limit of detection of IGFBP-3 was 0.1 mg/l and that of ALS was 0.25 mg/l; the intra-and interassay coefficients of variation (CV) for IGFBP-3 were 6.2% and 11.9% (13) respectively, and those for ALS were 3.4% and 10.5% respectively (14).…”
Section: Hormone Assaysmentioning
confidence: 99%